Lateral circumflex femoral artery false aneurysm as a complication of intertrochanteric hip fracture with displaced lesser trochanter. Issue 6 (18th June 2019) - Arbeloa-Gutierrez, Lucas; Arenas-Miquelez, Antonio; Muñoa, Leyre; Gordillo, Ainhoa; Eslava, Eunate; Insausti, Iñigo; Martínez de Morentin, Javier
Abstract: We present a patient who suffered an unstable intertrochanteric hip fracture and underwent osteosynthesis with a trochanteric nail. During the postoperative period, he presented a pseudoaneurysm of the lateral circumflex branch of the deep femoral artery secondary to a displaced fracture of the lesser trochanter. With the suspected diagnosis due to indirect clinical and radiological signs and confirmation by Doppler ultrasound and computed tomography angiography, a transverse arterial embolization with resolution of the symptoms was carried out. The pseudoaneurysm of the deep femoral artery or its branches is a very rare complication after intertrochanteric hip fractures, which must be taken into account in the late appearance of edema and hematoma in the thigh and evidence of medial and superior displacement of the lesser trochanter. The diagnosis is confirmed by CT angiography and the treatment by percutaneous arterial embolization has good results without the need of excising the lesser trochanter.